Immunohistochemical Expression Profile of P16 In Cervical Carcinoma Patients At Siloam Mrccc Cancer Hospital In 2022 - Ani Oranda Panjaitan; Fajar Lamhot Gultom; Clariza Ovelyn Iona Rombe (International Journal of Health and Pharmaceutical (IJHP), 2026)
Cervical carcinoma is a rapidly growing health issue, with global cases reaching 662,301 and causing 348,874 deaths in 2022. Almost all cervical carcinoma cases are associated with persistent Human Papillomavirus (HPV) infection. The cell cycle-dependent kinase inhibitor (p16) serves as a reliable surrogate biomarker for HPV-associated cervical carcinoma. This descriptive observational study analyzes the dataset from the academic file "Ani Oranda Panjaitan_Fajar Lamhot Gultom.docx", which examines the immunohistochemical expression profile of the p16 protein in cervical carcinoma patients at Siloam MRCCC Cancer Hospital in 2022. Out of 42 archived cases, squamous cell carcinoma (SCC) was the dominant subtype with 34 cases (81%), followed by adenocarcinoma and adenosquamous carcinoma with four cases (9.5%) each. From the 32 patients who met the strict inclusion criteria for immunohistochemical staining, 30 patients (93.75%) demonstrated positive p16 expression, confirming a high prevalence of HPV-associated cervical carcinoma. Conversely, two patients (one SCC and one adenocarcinoma) showed negative p16 results. These findings indicate that over 93% of cervical carcinoma cases at this facility are directly associated with HPV, with SCC remaining the predominant subtype. Further research is needed to expand the sample size and integrate PCR HPV genotyping to monitor viral presence.